Development of an information system for teleoperated physical rehab care service via Internet. Pilot case: patients with mild knee injury who live in geographically vulnerable zones (2018)
In recent years, new technologies have been implemented for treating and rehabilitating of diseases, such as distance medicine, known as telemedicine. With the participation of an interdisciplinary group of researchers from Universidad del Valle and health professionals, a pilot project was established to test a teleoperated care system with a prototype designed for the rehabilitation of patients with mild knee injury in the of public health network ESE Ladera in Cali, Colombia, to provide physical rehabilitation services from the urban health center to patients living in rural areas of Cali. In order to comprehensively evaluate the functioning of this teleoperated physical rehabilitation system comprenhensively, an information system (IS) was designed that includes a set of indicators that assess the health care system from a mechanical, economic, clinical and social points of view.